Determinant of Intrauterine Contraception (IUD) Election on Couples of Childbearing Age - Ika Lestiani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
The crucial problem in our country is a population explosion, so the Government made a program called family planning (FP) which have the vision to be a qualified family that safe healthy, advance, and independent. Also have the ideal child with the brilliant concept, responsibility, harmony, and religious. The research direction to study and tell the determinant that related to the election of intrauterine contraception tools in UPT II Region of Banjar regency in 2014. The research use case-control design with retrospective approached a sample quantity is 206 respondent that divided as 103 (IUD acceptor) and 103 (non-IUD acceptor), also statistic analysis uses the chi-square and logistic regression. The variable that related to the election of IUD contraception on couples of childbearing age is age, education, parity, FP services, husband support, knowledge, application cost (p-value<0.05), and the non-related variable is an occupation and economic status. Based on logistic regression test, we have a result that the most related factor to an election of IUD contraception on couples of childbearing age is education with the p-value 0.000 and odds ratio (OR) 5.971. That means is couples of childbearing age with the higher education have 5,9 times has an opportunity to use the IUD contraception, after controlling for the variable to husband support, as well as age, parity becomes confounding variables.